Survival and growth of Vibrio cholerae O139 in selected Malaysian street foods - Rusul, Gulam; Chun, Chong Kam; Radu, Son (Intemational Association of Milk, Food and Environmental, 1997)
The growth of Vibrio cholerae O139 inoculated into cendol (a mixture of coconut milk, brown sugar, and green jelly from rice flour), rojak (prawn paste, sugar, soy sauce, spices, garlic, and peanut gravy), gravy, tofu, fried tofu, and wheat-flour noodles (all except rojak gravy containing the natural microbial flora) was examined at four incubation temperatures (7, 15, 25, and 35°C). V. cholerae O139 grew well in cendol incubated at 25 and 35°C but not at 15°C or below. No growth of V. cholerae O139 in rojak gravy was detected at any temperature except for very slow growth at 35°C. V. cholerae O139 inoculated into tofu exhibited slow growth at 25 and 35°C and growth was not detected at 7 and 15°C. However, in fried tofu, the organism entered the growth phase after 12 h of incubation at 25 and 35°C. Growth of V. cholerae O139 was not demonstrated in noodles at any incubation temperatures. Nutrient broth with 1% NaCl added supported the growth of V. cholerae O139 at 25 and 35°C. At both of these incubation temperatures mean generation time was longer at pH 5 than at pH 8. The high variation in growth of V. cholerae O139 in the distinct foods examined might have been due to differences in pH, fat content, and a(w). Proper sanitary practices and storage of foods at refrigeration temperatures will help to reduce the possibility of growth by Vibrio cholerae O139 in foods to levels which do not imply a risk for food-poisoning.